A ratiometric fluorescent probe for rapidly detecting bio-thiols in vitro and in living cells. (December 2019) - Mao, Yueyuan; Du, Huanhuan; Wang, Xuchun; Tian, Meng; Wang, Yang; Liu, Lei; Wei, Jumeng; Xue, Fengfeng; Liu, Guodong; Zhang, Xueji; Yi, Tao
Abstract: Bio-thiols play an important role in living organisms. Both elevated levels and deficiency of bio-thiols will induce some diseases, such as cardiovascular disease and Alzheimer's diseases, skin lesions, and weakness. Therefore, fast and accurate detection of bio-thiols is of great significance. We have synthesized a ratiometric probe that can respond to bio-thiols with the fluorescence intensity at 568 nm ( F 568 ) increasing and taht at 420 nm ( F 420 ) decreasing. The responding process reaches equilibration in 1 min in the present of Cys or Hcy while in about 50 min with GSH. This probe can further detect bio-thiols in human breast cancer cells (MDA-MB-231) by confocal laser scanning microscope. Fluorescent ratio ( R Y/B ) of yellow channel with blue channel increase as reacting with bio-thiols in cells. Ratiometric probeSH-1 can realize the fast detecting of bio-thiols with R Y/B as detection signal both in vitro and in living cells. Graphical abstract: Image 1 Highlights: Rapidly respond to Cys or Hcy and F 568 reach the highest intensity in 1 min. Imaging bio-thiols with R Y/B as detection signal in living cells and R Y/B shows obvious change (form <5 to >40). Both the probeSH-1 and responding productSH-1-P are low toxicity.